Survey theopinions professional and academics on building the strategy of internal audit function and the possibility of keeping abreast of developments (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research problem is clearly deficient suffered by the internal audit function in all institutions of Iraq, as a result of the lack of sponsor organizations for this profession and there is no law or local legislation determine its powers and its responsibilities and scope of work As well as the lack of interest of senior management in economic units that function, as it focuses its work on the scope of financial and accounting matters only So required to rebuild this function in line with the current developments as well as the lack of a framework that defines the strategy of this function, and it came the idea of research to find out how to create a regulatory method for re-strategic construction of the internal audit function depending on the standards internal IIA InstituteAnd taking into account a framework COSO and COBIT, and Sarbanes-Oxley Act,surveyed a sample of accountants, academics and professionals working in the sector, states and the private sector and the views of auditors as well as members of the boards of some companies in Iraq, about the status of a proposed framework for the internal audit function.